High frequency hearing loss may act as a screening index evaluating otolith function in vertigo patients with normal semi-circular canal function - Tian, Liang; Chen, Zhongchun; Wang, Jinyu; Zhang, Lei; Zhao, Hao; Chi, Fanglu; Wang, Jing (Frontiers in Neurology, 2022)
Objective: To investigate whether otolith dysfunction is related to hearing impairment in vertigo patients with normal semicircular canal function, and to clarify the types of hearing impairment that may be related to otolith organ damage. Methods: The demographic data, pure tone threshold audiometry (PTA) results (air-conduction), data of bithermal and video-head impulse test (vHIT), and vestibular evoked myogenic potential (VEMP) results (reaction threshold, P1-N1 amplitude) of patients with vertigo in outpatient clinic from April 2017 to January 2020 were collected. The clinical records of 51 vertigo patients with normal semicircular canal function were included in this study. Low-frequency, speech-frequency, high-frequency, full-frequency PTA were defined as the average of PTA in different frequency bands respectively (low: 0.125, 0.25, 0.5 kHz; speech: 0.5, 1, 2kHz, high: 4,8kHz, full 0.125-8 kHz). The correlations between hearing impairment in different frequency bands and otolith function impairment were analyzed. Results: The mean thresholds of 51 patients (102 ears) in low-PTA, speech-PTA, high-PTA, full-PTA were 20.95±6.01, 21.92±6.90, 40.12±17.47, 26.97±8.53 dB nHL respectively. Among 102 ears, 87 ears (85.3%) could elicit c-VEMP waveforms and 65 ears (63.7%) had o-VEMP waveforms. The mean threshold and P1-N1 amplitude of c-VEMP were 83.10±6.96dB nHL and 176.79±103.10 uV, while those of o-VEMP were 87.92±5.99dB nHL and 21.45±32.22 uV. The mean threshold in high-PTA was significantly linearly correlated with c-VEMP threshold (P=0.01) and P1-N1 amplitude (P=0.028). There were not significant linear correlations between the mean threshold in each frequency band of PTA and o-VEMP threshold (low-PTA: P=0.266, speech-PTA: P=0.33, high-PTA: P=0.311) or P1-N1 amplitude (low-PTA: P=0.414, speech-PTA: P=0.069, high-PTA: P=0.08). Conclusions: There is a positive linear correlation between saccule dysfunction and high-frequency hearing impairment in vertigo patients with normal semi-circular canal function. High frequency hearing loss can be expected in patients who have saccular damage. It suggests that high frequency hearing loss in PTA may act as a screening index that otolith organ function should be comprehensively evaluated.